Answer:
Option C.
Step-by-step explanation:
Note : In the given points one point is (8,-2) instead of (-6,-2).
The standard form of a circle is
[tex](x-h)^2+(y-k)^2=r^2[/tex]
where, (h,k) is center of circle and r is radius.
It is given that center of the circle is (-1,-2). So,
[tex]h=-1,k=-2[/tex]
[tex](x-(-1))^2+(y-(-2))^2=r^2[/tex]
[tex](x+1)^2+(y+2)^2=r^2[/tex] ...(1)
It is given that the circle passing through the point (8,-2),(-1,5),(6,-2),(-1,-9).
Substitute x=6 and y=-2 in equation (1).
[tex](6+1)^2+(-2+2)^2=r^2[/tex]
[tex](7)^2+(0)^2=r^2[/tex]
[tex]49=r^2[/tex]
Substitute [tex]r^2=49[/tex] in equation (1).
[tex](x+1)^2+(y+2)^2=49[/tex]
Therefore, the correct option is C.